Neural and fuzzy herarchical approaches for clustering of molecular structures with overlapping activities [compact disc] - 353753 Jehan Zeb; Naomie Salim, supervisor (Skudai : Universiti Teknologi Malaysia, 2008)
Thesis (Doktor Falsafa (Fakulti Sains Komputer)) - Universiti Teknologi Malaysia, 2007